Injuries of the vulva and vagina in childhood - Okur, Hasan; Zorludemir, Ünal; Yücesan, Selçuk; Olcay, Işık (The Turkish Journal of Pediatrics, 1990)
Injuries of the vulva and vagina are relatively rare in children. Over a seven-year period, we treated 45 girls. The most common etiologic factor in our study group was trauma. While 28 had only vulvar lesions, the rest had injuries of both the vulva and vagina. Thirty-two children were treated surgically for only vulvar and vaginal injuries. However, additional organ treatment was mandatory for 13 children.